Efeito do tamanho de partículas de Cu nas propriedades estruturais e eletrônicas e suas correlações com propriedades catalíticas na desidrogenação do etanol em Cu/SiO2 - Osmari, Taynara Andrea (Universidade Federal de São Carlos, 2019)
Metal nanoparticles may exhibit distinct catalytic behavior when there are particle size variations at nanometric scale. Cu nanoparticles supported on SiO2 and CAB-O-SIL® were synthesized with different metal loadings by ammonium evaporation method in order to evaluate the particle size effect on the structural and electronic properties in the ethanol dehydrogenation to acetaldehyde reaction. Because this reaction is structure-sensitive, it has the activation of the O-H bond, which is the determining step, favored by a higher electronic density of the metallic center, characteristic of very small particles. Thus serving as a model reaction to evaluate the behavior of Cu0 sites. The synthesized catalysts were characterized by: i) evaluation of structural properties through XRD, TPR-H2, TPR-N2O, TEM, and EXAFS; ii) evaluation of electronic properties by FTIR-CO, XPS, and XANES; and iii) evaluation of kinetic parameters by DFT. The structural and electronic properties were correlated with the catalytic activity (TOFAcH) and apparent activation energy (Eap). The Cu/SiO2 catalysts presented smaller particles, higher dispersion, and lower reduction degrees than Cu/Cab. For both series, the presence of Cu-O scattering particles with Cu-Cu coordination number (NCu-Cu) below 8 was observed. Moreover, FTIR-CO and XANES results indicated increased Cu+ when NCu-Cu decreased with the Cu-Cu bond distance (RCu-Cu) of 1.842 (NCu-Cu = 4.4; NCu-O = 0.8) to 1.849 Å (NCu-Cu = 7.9; NCu-O = 0.3), which is less than RCu-O from the Cu2O bulk (RCu-O = 1.855 Å). Data of EXAFS and FTIR-CO suggest that Cu nanoparticles are formed by a core-shell structure. The contraction in RCu-O occurs with the presence of surface O interacting with Cu+ in the Cu core surface. Values of TOFAcH correlated with NCu-Cu suggest increased activity with increased particle size, which is contrary to expectations. However, the decrease of NCu-Cu results increased surface O and decreased RCu-O. The values of TOFAcH decreased and Eap increased with the decrease of RCu-O and NCu-Cu, demonstrating that the presence of surface O causes decreased electronic density of Cu0 sites. Data from DFT indicated higher ethanol heat of adsorption (ΔHEtOH) for clusters without surface O (13Cu: -51.92 kJ.mol-1) than clusters with O (13Cu4O: -26.97 kJ.mol-1), while the energy of the transition state for ethoxide formation remained constant. The results suggest that the relevant step for the activation of ethanol is the adsorption of ethanol, which is highly sensitive to the presence of O on the surface.
Keywords: Nanopartículas de cobre; Desidrogenação do etanol; Tamanho de partícula; Propriedades eletrônicas; Propriedades estruturais; Copper nanoparticles; Particle size; Eletronic properties; Structural properties; EXAFS; Ethanol dehydrogenation; ENGENHARIAS::ENGENHARIA QUIMICA